Distribution of bovine alpha-herpesviruses and expression of toll-like receptors in the respiratory system of experimentally infected calves - Marin, Maia Solange; Quintana, Silvina; Leunda, Maria Rosa; Odeon, Anselmo Carlos; Perez, Sandra (Elsevier, 2019)
This study provides an initial analysis of the toll-like receptors (TLRs) that might be implicated in alpha-herpesvirus infection of the bovine respiratory system. A significant variation in the expression of TLR3 and TLRs 7–9 during bovine herpesvirus type 1 (BoHV-1) and 5 (BoHV-5) acute infections and particularly an up-regulation during viral reactivation in respiratory tissues has been demonstrated. Furthermore, viral distribution in the respiratory tract of BoHV-1- and BoHV-5-infected calves at different stages of the infectious cycle was analysed. The wide distribution of BoHV DNA in the respiratory tract during acute infection was restricted during latent infection and the subsequent reactivation of BoHV-1 and BoHV-5. Overall, the findings presented here contribute to the knowledge on the replication and dissemination of bovine alpha-herpesviruses. Furthermore, some of the immune factors triggered in the host that determine the different outcomes of infection by two closely related pathogens of cattle have been elucidated.